The Influence of Minimalism in Contemporary Art Thought on Visual Communication Design - Pei, Zixuan (Transactions on Social Science, Education and Humanities Research, 2023)
Contemporary art trends have various influences on visual communication design in modern art design, and they influence each other and develop together in this era of art. In the diversified background of today’s world, art trends are constantly influencing contemporary art design. As an extremely important school of Western modern art that emerged in the 1960s, Minimalism is the only one that has been able to develop in the United States. It is one of the last schools of modernism that has had a significant impact on art and design around the world. Minimalist style highlights the characteristics of art style is calm and objectivity, which is not mixed with a trace of personal emotion, it has played an influential role in the concept of contemporary visual communication design and artistry, which in turn has played a driving role in the development of contemporary visual communication design.